Spermatic Cord Knot: A Clinical Finding in Patients with Spermatic Cord Torsion - Abdullatif Al-Terki; Talal Al-Qaoud (Advances in Urology)
Pertinent history taking and careful examination often taper the differentials of the acute scrotum; congruently the ability to diagnose acute spermatic cord torsion (SCT) when radiological adjuncts are not available is highly imperative. This observational study serves to present a series of 46 cases of spermatic cord torsion whereby we hypothesize the identification of a clinical knot on scrotal examination as an important clinical aid in making a decision to surgical exploration in patients with acute and subacute SCT, especially in centers where imaging resources are unavailable.